Transition to the knowledge-based economy in the public sector - Pronina Z. Ю. (Interactive science, 2018)
the world economy has undergone profound changes in recent years, resulting in the emergence of the new economy, the knowledge-based economy. The development of knowledge is becoming increasingly important for the public sector. This determines the need for a comprehensive study of the knowledge society. Within the knowledge-based economy, public sector requires the use of knowledge to improve the transparency and effectiveness of public services provided to citizens. The transition to the knowledge-based economy in the public sector should be carried out in a decentralized manner, without unnecessary bureaucratic delays and effectively
Keywords: инновации; экономика знаний; управление знаниями; innovation; public sector; государственный сектор; knowledge-based economy; knowledge management